Pembuatan Film Pendek Berjudul ‘Jangan Menyerah’ Dengan Menggunakan Kamera Smarphone - Darmoyo Darmoyo (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2020)
Capturing and recording images in making a film is not only done by pro cameras such as various kinds of camcorder video cameras and DSLR-type video cameras. In addition to its use requiring special expertise for the wearer, the video camera has various features or parts that are rather complicated in its operation and settings. The presence of video cameras found on smart phones, can provide an alternative for users in the process of taking and recording images that are more practical, fast and efficient. Although the results of images or videos produced through smart phone video cameras are not as good as when compared to using a more pro video camera.